Análise histomorfométrica e da citotoxicidade de uma biocerâmica de fosfato de cálcio obtido a partir da casca de ovo de galinha para engenharia tecidual - Nascimento Neto, Conrado Dias do Nascimento (2023)
Goal: To investigate the cytotoxicity and effect on tissue repair of a hydroxyapatite/dicalcium phosphate anhydrous (HA/DCPA) material obtained from chicken eggshell compared to the commercially available maxresorb® (MXR). Methods: Cytotoxicity was evaluated in fibroblasts (L cell, L-929) by the MTT test. Tissue repair was evaluated after grafting of biomaterials into critical-sized bone defects (CSDs) trephined in the calvarial bones of 24 Wistar rats. The animals were euthanized after 30, 60, and 90 days and the bone specimens containing the graft area were examined by scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS) (n=3), and histologic and histomorphometric analyses (n=21). The percentages of newly formed bone, connective tissue, remaining biomaterial, and total tissue repair area were compared between groups using Student’s t-test and ANOVA (p≤0.05). Results: HA/DCPA did not exhibit any cytotoxicity. Histologically, the CSDs contained newly formed bone from the defect margins and from ossification centers interspersed throughout the biomaterials. At 30 days, animals in the HA/DCPA group had a larger total tissue repair area than those in the MXR group (p=0.047), due to preservation of newly formed bone, connective tissue, and remaining biomaterial within the CSDs. No differences were observed between the experimental groups regarding percentage of newly formed bone, connective tissue, and remaining biomaterial at the time points of observation (p>0.05). Conclusions: Chicken eggshell-derived HA/DCPA is devoid of cytotoxic potential and can induce new bone formation and complete tissue filling of critical-sized bone defects with a degree of biomaterial degradation to the same extent as MXR.